2015
DOI: 10.1007/s00701-015-2495-4
|View full text |Cite
|
Sign up to set email alerts
|

Intracranial meningiomas and seizures: a review of the literature

Abstract: Seizures are a common manifestation of meningiomas, but about 80 % patients with preoperative seizures can be seizure free after tumor removal. Prospective controlled AED trials specifically on meningioma patients are much needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
17
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 55 publications
4
17
0
3
Order By: Relevance
“…Moreover, Mantle et al 11 reported a strong association between brain-invasive growth and PTBE, which is one of the main risk factors for the development of perioperative seizures. 4,6,12,23 In the same series, the authors found a 20% increase in the incidence of brain invasion with each 1-cm increase in edema. 11 Disruption of cortical integrity by infiltrating meningioma cells with subsequent astrocytic response 24 might also impair neurological function and contribute to an increased risk of seizures in patients with brain-invasive meningioma.…”
Section: Discussionmentioning
confidence: 78%
See 1 more Smart Citation
“…Moreover, Mantle et al 11 reported a strong association between brain-invasive growth and PTBE, which is one of the main risk factors for the development of perioperative seizures. 4,6,12,23 In the same series, the authors found a 20% increase in the incidence of brain invasion with each 1-cm increase in edema. 11 Disruption of cortical integrity by infiltrating meningioma cells with subsequent astrocytic response 24 might also impair neurological function and contribute to an increased risk of seizures in patients with brain-invasive meningioma.…”
Section: Discussionmentioning
confidence: 78%
“…The frequency of preoperative seizures in our study was 19%, which is in line with the broad range of incidences reported from previous analyses. 4,6,12,23 According to findings in macroscopically detected brain-invasive meningiomas, 5 the incidence of preoperative seizures was distinctly higher in patients with a microscopically detected brain-invasive meningioma than in those with a noninvasive meningioma. Correspondingly, seizures were more common in patients with a high-grade than in those with a benign meningioma.…”
Section: Brain Invasion and The Risk Of Preoperative Seizuresmentioning
confidence: 99%
“…[10] Yine semptomlu menenjiomların %40'dan fazlası ameliyattan önce nöbet ile prezente oldukları saptanmıştır. [6] Bizim çalışmamızda kranyal intrakraniyal cerrahi geçiren hastalarda nöbet etiyolojisinde YKL'ler ilk sırayı almış olup bunu BDH ve travmalar ikinci sıklıkla takip etmiştir. Beyin tümörlü hastaların yaklaşık %30'unda ilk semptomu nöbettir.…”
Section: Discussionunclassified
“…[5] Literatürde semptomlu menenjiomların %40'dan fazlasının ameliyattan önce nöbet ile prezente oldukları saptanmıştır. [6] Kafa travmasının, çeşitli spektrumlarda motor ve kognitif özürlülük gelişimine neden olabildiği, nöbetlerin ise sık ortaya çıkan komplikasyonu olduğu bildirilmiştir. [7] Yapılan çalışmada cerrahi sonrası nöbet gelişimi açısından risk faktörleri olarak ameliyat öncesi nöbet olması, tümörün yeri, geniş tümör rezeksiyonu belirtilmiştir.…”
Section: Introductionunclassified
See 1 more Smart Citation